2011
DOI: 10.1038/ejcn.2011.189
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and macronutrient intake patterns are related to general and central adiposity

Abstract: Background/Objectives: Alcohol and dietary fat have high energy densities and may therefore be related to body weight and fat deposition. We studied associations between alcohol and macronutrient intake patterns and general and central adiposity. Subjects/Methods: A population-based cross-sectional study of 524 men and 611 women. The participants answered a dietary questionnaire describing habitual food consumption including intake of alcoholic beverages. Macronutrient intake was analysed in relation to anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
2
26
0
2
Order By: Relevance
“…None of these studies however evaluated the effect of substituting a proportion of any macronutrient intake with that of another. In line with our finding, observational studies have shown a positive association of protein intake with percent body fat [ 23 , 24 , 25 ]. In a prospective study, a higher intake of dietary protein, substituted for either carbohydrate or fat, was found to be related to increased body weight and BMI after a six-year follow-up, an increase mainly attributed to increased body fat mass [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…None of these studies however evaluated the effect of substituting a proportion of any macronutrient intake with that of another. In line with our finding, observational studies have shown a positive association of protein intake with percent body fat [ 23 , 24 , 25 ]. In a prospective study, a higher intake of dietary protein, substituted for either carbohydrate or fat, was found to be related to increased body weight and BMI after a six-year follow-up, an increase mainly attributed to increased body fat mass [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Also, the current analyses did not control for race or socioeconomic factors. While we did control for gender, we were underpowered to fully evaluate gender differences, which have been shown to have a relationship with both sleep and eating patterns [2426]. Participants were recruited for their sleep timing preferences and were not randomly selected.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the limitations stem from our sample size, which limits our statistical power to observe associations. The analyses did not control for race or socioeconomic factors, and for gender but were underpowered to fully evaluate gender differences, which have relationships with both sleep and eating patterns (Brandhagen et al, 2012; Cornier, Salzberg, Endly, Bessesen, & Tregellas, 2010; Lauderdale et al, 2006). Participants were recruited for their sleep timing preferences, and were not randomly selected.…”
Section: Discussionmentioning
confidence: 99%